A Rhesus Monkey Model of Non-suicidal Self-Injury - Novak, Melinda A.; Meyer, Jerrold S. (Frontiers in Behavioral Neuroscience, 2021)
Nonsuicidal self-injury (NSSI) is a type of behavioral pathology seen not only in a variety of clinical conditions but also among nonclinical populations, particularly adolescents and young adults. With the exception of rare genetic conditions that give rise to self-harming behaviors, the etiology of NSSI and the events that trigger specific episodes of this behavior remain poorly understood. This review presents the features of an important, extensively studied animal model of NSSI, namely spontaneously occurring self-injurious behavior (SIB) in rhesus macaque monkeys. We compare and contrast rhesus monkey SIB with NSSI with respect to form, prevalence rates, environmental and biological risk factors, behavioral correlates, proposed functions, and treatment modalities. Many parallels between rhesus monkey SIB and NSSI are demonstrated, which supports the validity of this animal model across several domains. Determining the etiology of spontaneously occurring SIB in monkeys, its underlying biological mechanisms, and which pharmacological agents are most effective for treating the disorder may aid in identifying potential risk factors for the occurrence of NSSI in humans and developing medications for severe cases that are resistant to conventional psychotherapeutic approaches.